2018
DOI: 10.18632/oncotarget.26380
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and polymorphisms in pancreatic neuroendocrine tumors treated with sunitinib

Abstract: Several circulating biomarkers and single nucleotide polymorphisms (SNPs) have been correlated with efficacy and tolerability to antiangiogenic agents. These associations remain unexplored in well-differentiated, metastatic pancreatic neuroendocrine tumors treated with the multitargeted tyrosine kinase inhibitor sunitinib. We have assessed the effect on tumor response at 6 months, overall survival, progression-free survival and safety of 14 SNPs, and 6 soluble proteins. Forty-three patients were recruited. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Due to the rare nature of panNETs, it is challenging to recruit large numbers of patients for clinical trials and subsequent analyses. The genotyped population (n = 56) of our study was of a comparable size with other SNP studies in patients with panNETs, including studies by Jiménez-Fonseca et al (n = 43) [34], Karakaxas et al (n = 51) [36] and Cigrovski Berković et al (n = 60) [19]. Consequently, our analyses, like many SNP panNET studies, are also limited by the small sample sizes in some of the subgroups, as well as the exploratory nature of the study.…”
Section: Treatment-naive Previously Treated Combinedmentioning
confidence: 68%
See 2 more Smart Citations
“…Due to the rare nature of panNETs, it is challenging to recruit large numbers of patients for clinical trials and subsequent analyses. The genotyped population (n = 56) of our study was of a comparable size with other SNP studies in patients with panNETs, including studies by Jiménez-Fonseca et al (n = 43) [34], Karakaxas et al (n = 51) [36] and Cigrovski Berković et al (n = 60) [19]. Consequently, our analyses, like many SNP panNET studies, are also limited by the small sample sizes in some of the subgroups, as well as the exploratory nature of the study.…”
Section: Treatment-naive Previously Treated Combinedmentioning
confidence: 68%
“…Our analyses did not investigate VEGFR3 SNPs, reported by others to be correlated with a decreased tumor response to pazopanib [31], divergent tumor responses to sunitinib [18,20,25,[32][33][34] and poor prognosis in patients with gastroenteropancreatic neuroendocrine neoplasms [35]. A recent Spanish multicenter SNP analysis in patients with well-differentiated panNETs reported that VEGFR3 rs307826 and rs307821 predicted lower OS, but not PFS [34]; however, following correction for multiple testing, no correlations remained significant. Consistent with our study, no statistically significant correlation was observed between PFS or OS and the SNPs VEGFA rs2010963, ABCB1 rs1128503 or ABCB1 rs2032582 [34].…”
Section: Treatment-naive Previously Treated Combinedmentioning
confidence: 79%
See 1 more Smart Citation
“…In 43 patients treated with sunitinib, Jimenez-Fonseca has shown a better OS (p = 0.01) for AA-carriers compared to AG/GG-carriers. No significant impact on RR or PFS was observed, although the HR was in favor of the AA-carriers (0.70 for RR and 0.76 for PFS, respectively) [23]. In 44 patients with NETs from pancreatic origin, treated with pazopanib, Grande et al have shown a trend to better PFS (HR 0.14; p = 0.055) for AA-carriers compared to AG-carriers (12 versus 2 months, respectively).…”
Section: Discussionmentioning
confidence: 85%
“…This structure is sustained by a host of proangiogenic molecules, such as vascular endothelial growth factor receptors (VEGFR), platelet-derived growth factor receptor (PDGFR) and others. 2,3 As a result, PanNETs appear as hypervascular masses on computed tomographies (CT), with avid contrast enhancement in the arterial phase. 4 The intensity of radiological enhancement correlates with the microvascular density.…”
Section: Introductionmentioning
confidence: 99%